Penerapan Teknologi Restorasi Lamun Sebagai Upaya Mitigasi Degradasi Ekosistem Lamun di Kabupaten Pangkep - Mahatma Lanuru; Rohani Ambo Rappe; Supriadi Mashoreng; Khairul Amri; Yayu A La Nafie; Muh. Banda Selamat; Rasyid Jalil; Muh Hatta; Muh Lukman (Universitas Hasanuddin, 2023)
The Seagrass bed ecosystem is one of the essential ecosystems besides mangroves in the coastal area of ​​Pundata Baji Village. However, the knowledge of coastal communities (fishermen) on the Pundata Baji regarding seagrass ecosystems' physical, ecological, and socio-economic roles is still limited. In addition, these coastal communities do not yet have the knowledge and skills to restore the damaged seagrass habitat (degraded). Therefore, awareness-rising programs and training efforts are needed, as well as demonstration plots regarding community-based seagrass restoration technology through transplantation (planting). Seagrass transplant trials used the Staple, the Frame/TERFS, and the rock anchor methods. The three transplantation methods introduced are simple, inexpensive, easy to learn, and applicable to the target group. Community understanding and awareness of the importance of seagrass ecosystems have increased after attending counseling and training. In addition, coastal communities have skills in seagrass transplantation after attending the training. Another target achieved from the seagrass transplant pilot activity is the availability of alternative fishing areas in the seagrass planting area for fishermen groups in the Pundata Baji coastal area.